Optimalisasi Motivasi Berprestasi Dan Pendidikan Karakter Dampaknya Terhadap Prestasi Belajar Materi Himpunan Melalui Pendekatan Konstruktivisme Pada Siswa Kelas VII D SMP Negeri 3 Teras Kabupaten Boyolali Semester Gasal Tahun Pelajaran 2014/2015 - Suryana, Muh. Fakhrudin (Jurnal VARIDIKA, 2014)
The purpose of the study is describing the achievement motivation, charac- ter education, and learning achievement. The research subject are 30 students of VII D grade, SMP Negeri Teras Boyolali. Data collection method used observation, ques- tionnaires, documentation, and testing. Data analysis used a critical and comparative analysis. Indicators of learning success is passing grade, Research procedures and 100% class attedance used cycles. Results of research and discussion shows that: 1) Consrtruc- tivism approach,  help optimising the readiness of teachers in the learning of the initial conditions to the first cycle of 17.1%, then from the first cycle to cycle II, an increase of 30% as well as from the initial condition to a second cycle of 47.1%; 2) Through consrtructivism approach can optimize the preparation class for learning from the initial conditions to the first cycle of 26%, then from the first cycle to the second cycle there is an increase of 22% as well as from the initial condition to the second cycle by 48%;3) Through consrtructivism approach can optimize the achievement motivation of the initial conditions to the first cycle there is an increase student achievement of grade of 23%, from the first cycle to cycle II, an increase of 20%, and of the initial conditions of the second cycle to an increase of 43%; 4) Consrtructivism approach can optimize the educational character of the initial conditions to the first cycle there is an increase of 13% grade achievement, from the first cycle to cycle II, an increase of 20%, and of the initial conditions of the second cycle to an increase of 33%; 5) Consrtructivism approach can optimize student achievement of the initial conditions to the first cycle there is an increase of 20% grade achievement, from the first cycle to cycle II, an increase of 20%, and of the initial conditions of the second cycle to an increase of 40%; 6) through kon- srtruktivisme approach can optimize achievement motivation, character education, and mathematics achievement assemblage material, because students are able to construct their own knowledge, although it can not be separated from the guidance of a teacher